Understanding the menstrual health self-care practices and experiences among women with physical disabilities in rural Nepal: A qualitative study - Suyasha Adhikari; Pabitra Neupane; Anisha Shrestha; Manasi Sharma; Karishma Bhandari; Amit Timilsina (PLoS ONE, 2025)
Background Women with disabilities often face significant challenges in promoting and practicing menstrual health, which compromises their quality of life and overall well-being. Limited studies have been conducted on women with physical disabilities and their self-care practices related to menstrual health in rural Nepal. Thus, this study aims to explore the differential experience and self-care practices for menstrual health among married women with physical disabilities in Karnali Province of Nepal. Methods The study used an exploratory qualitative method utilizing purposive sampling. Data collection was conducted through in-depth interviews and focus group discussions, in which 31 married women with disabilities participated. A thematic analysis approach was employed, in which codes were generated inductively and organized into sub-themes, then consolidated into themes, which were subsequently presented as the findings supported by excerpts. Result The majority of the participants relied on gut feelings, and bodily symptoms such as head itches, mood swings, an increase in body temperature, home remedies for period cramps, and self-examination of the colour, odour, and consistency of menstrual blood for self-management. Participants self-tested for pregnancy in case of missed period while self-monitoring their blood pressure and menstrual blood for health diagnosis. The participants had misconceptions such as passing on disability to their fetus due to pain-management medication, practiced seclusion, avoided consumption of dairy products, fruits, and foods, and had limited knowledge, access, and misinformation regarding menstrual products beyond cotton clothes and menstrual pads, which suggests low self-awareness regarding menstrual health management. Conclusion Access to disability-inclusive menstrual health information through optimal utilization of digital platforms and community sensitization events, knowledge and access to diverse menstrual product choices, mobilization of community volunteers for social and behaviour change initiatives, and the self-care inclusive health policies promoting social protection and menstrual health self-care provisions are key for decreased sexual and reproductive morbidity, and improved quality of life among women living with disability.